PENERAPAN SYSTEM STANDAR COSTING SEBAGAI ALAT PENGENDALIAN BIAYA PRODUKSI PADA PT KEMAS ANUGERAH SWANTIKA MEDAN - yulianty yulianti; Retnawaty Siregar (Universitas Medan Area, 2015)
The purpose of this study was to obtain concrete evidence of the application of the standard fee as a means of controlling production costs at PT. Pack Award Swantika Medan. This research is a descriptive study. The type of data the researchers used in this research is quantitative data, while the source of the data obtained from secondary data. Data collection techniques that researchers use in this study are engineering documentation and interview techniques. To mendiskrispsikan results in this study, researchers used the analytical technique with the accounting approach by applying the standard cost system to control production costs. Based on the formulation of the problem that has been raised is known that the company use the standards as a tool for planning and controlling production cost efficiently as possible to achieve the level that would maximize overall company operations and the presence of standard costs, expenses for the allocation of production costs at PT. Pack Award Swantika field can be controlled carefully.